Intralobar pulmonary sequestration - Parma, Dante; Yametti, Luis; Martinez, José L.; Delgado, Bolivar (Cirugía del Uruguay, 1979)
The paper describes a case of Intralobe Pulmonary Sequestration Diagnosis was mostly based on arteriography and treatment consisted surgery which, according to the authors, should be lobectomy.